Cellular calcium (Ca2+) buffers - Schwaller, Beat (Henry Stewart Talks, 2013)
The Ca2+ signaling toolkit, The EF-hand family of Ca2+-binding proteins, Biophysical properties of Ca2+ buffers determine their function, Ca2+ buffers as intracellular Ca2+ signal modulators, The «slow» buffer parvalbumin (PV) affects fast-twitch muscle function, Ca2+ buffers modulate short-term plasticity of synaptic transmission, Phenotypes of Ca2+ buffer knockout mice, The Ca2+ homeostasome